2021
DOI: 10.1038/s41467-021-22617-y
|View full text |Cite
|
Sign up to set email alerts
|

Loss of endothelial glucocorticoid receptor accelerates diabetic nephropathy

Abstract: Endothelial cells play a key role in the regulation of disease. Defective regulation of endothelial cell homeostasis may cause mesenchymal activation of other endothelial cells or neighboring cell types, and in both cases contributes to organ fibrosis. Regulatory control of endothelial cell homeostasis is not well studied. Diabetes accelerates renal fibrosis in mice lacking the endothelial glucocorticoid receptor (GR), compared to control mice. Hypercholesterolemia further enhances severe renal fibrosis. The f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 63 publications
1
83
0
Order By: Relevance
“…Interestingly, the glucocorticoid receptor (GR) signaling also plays a protective role in DN. A recent study showed that endothelial deletion of GR accelerates fibrosis in DN by enhancing EndoMT [147]. Mechanistically, GR suppresses TGF-β/Smad3 signaling by physically interacting with Smad3 protein and inhibiting its activity [148].…”
Section: Treatment Of Dn By Targeting Tgf-β Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the glucocorticoid receptor (GR) signaling also plays a protective role in DN. A recent study showed that endothelial deletion of GR accelerates fibrosis in DN by enhancing EndoMT [147]. Mechanistically, GR suppresses TGF-β/Smad3 signaling by physically interacting with Smad3 protein and inhibiting its activity [148].…”
Section: Treatment Of Dn By Targeting Tgf-β Signalingmentioning
confidence: 99%
“…Therefore, GR may serve as an inhibitor of Smad3. However, the GR agonist dexamethasone shows unfavorable side effects to exacerbate hyperglycemia [147].…”
Section: Treatment Of Dn By Targeting Tgf-β Signalingmentioning
confidence: 99%
“…Pathological stimuli such as inflammation, diabetes and ageing influence EndMT events in the kidneys [ 69 ]. Endothelial SIRT3, the nuclear receptor glucocorticoid receptor (GR) and cell surface FGFR1 are critical regulators of TGFβ signaling and EndMT in diabetic kidneys [ 70 , 71 , 72 , 73 ]. The kidneys of diabetic mice showed both progressive glomerular sclerosis and tubulointerstitial fibrosis, which was associated with approximately 40% of all FSP-1-positive cells and 50% of αSMA-positive stromal cells were CD31-positive [ 74 ].…”
Section: Lncrnas Involvement In the Regulation Of Endmtmentioning
confidence: 99%
“…Glucocorticoid receptors (GR) are essential for endothelial cell homeostasis and regulate defective metabolism in endothelial cells. Endothelial GR regulates renal fibrogenesis by targeting Wnt signaling, defective fatty acid oxidation and associated mesenchymal activation in diabetic kidneys (Srivastava et al, 2021b). In this issue, the authors discuss new cellular mechanisms and cell signaling in the regulation of DKD pathogenesis.…”
Section: New Cellular Mechanisms In Dkdmentioning
confidence: 99%